A Choice Based Experiment of Community Supported Agriculture (CSA): A Valuation of Attributes. (15th April 2018) - Yu, Qiushuo; Campbell, Ben; Liu, Yizao; Martin, Jiff
Abstract : Community-supported agriculture (CSA) operators are becoming more innovative in their efforts to attract consumers to become CSA shareholders. Therefore, CSA operators must understand which attributes consumers value. Using an online survey of Connecticut consumers in conjunction with a choice experiment, we evaluate consumer preference and willingness to pay for various attributes, including risk mitigation. We find younger consumers are more likely to prefer CSAs with organic products, while a greater diversity of products in the CSA share will increase preference for a CSA for some consumers. Further, we find that consumers with and without CSA experience value the risk-mitigation attribute.